Predictive Value of Pleural Cytology in the Diagnosis of Complicated Parapneumonic Effusions and Empyema Thoracis - Ferguson, John; Kazimir, Michal; Gailey, Michael; Moore, Frank; Schott, Earl (Pulmonary Medicine, 2020)
Introduction. Complicated parapneumonic effusions (CPE) are distinguished from uncomplicated parapneumonic effusions (UPE) by the ability to resolve without drainage. Determinants include pleural pH, pleural glucose, and pleural LDH, along with microbiologic cultures. Inflammation mediated by neutrophil chemotactic cytokines leads to fibrinous loculation of an effusion, and the degree of this inflammation may lead to a CPE. One role of the pathologist is to evaluate for the presence of malignancy in a pleural effusion; however, the ability of the pathologist to distinguish a CPE from UPE has not been evaluated. Materials and Methods. A single-center retrospective study was performed on pleural cytology specimens from 137 patients diagnosed with a parapneumonic effusion or empyema over a five-year interval. Pleural cytology was characterized as either uncomplicated or complicated by two pathologists based on cellular composition and the presence or absence of fibrinous exudate in the fluid. Cohen’s kappa was calculated for interobserver agreement. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of cytologic diagnoses were calculated. Determinants of cytologic accuracy were assessed using Wilcoxon rank sum test, unpaired t-test, and logistic regression. Results. Kappa interobserver agreement between pathologists was 0.753. Pleural fluid cytology sensitivity, specificity, PPV, and NPV for CPE/empyema were 76.0%, 95% CI [65.0, 84.9]; 50%, 95% CI [29.1, 70.9]; 83.3%, 95% CI [76.7, 88.4]; and 38.7%, 95% CI [26.5, 52.5], respectively. The presence of pleural bacteria, elevated pleural LDH, and reduced pleural pH were nonsignificant determinants of cytologic accuracy. Logistic regression was significant for the presence of pleural bacteria (p=0.03) in determining a successful cytologic diagnosis. Conclusion. Pleural cytology adds little value to traditional markers of distinguishing a UPE from CPE. Inflammation on pleural fluid cytology is suggestive of empyema or the presence of pleural fluid bacteria.